2014
DOI: 10.3945/ajcn.114.092551
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of probiotics on enteral nutrition in preterm neonates: a systematic review

Abstract: Probiotics reduced the time to full enteral feeds in preterm neonates. Additional research is necessary to assess the optimal dose, duration, and probiotic strain or strains used specifically for facilitating enteral nutrition in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 83 publications
3
56
0
4
Order By: Relevance
“…We acknowledge that the introduction of probiotics is a potential confounder. It is possible that both by a direct beneficial effect of probiotics on the immune system 31 and by reducing times to full feeds, 32 probiotics may have reduced CLABSI in vulnerable infants by reducing the need for or dwell time of central lines.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the introduction of probiotics is a potential confounder. It is possible that both by a direct beneficial effect of probiotics on the immune system 31 and by reducing times to full feeds, 32 probiotics may have reduced CLABSI in vulnerable infants by reducing the need for or dwell time of central lines.…”
Section: Discussionmentioning
confidence: 99%
“…Pending the results of these studies, other strategies, such as probiotic or prebiotic supplementation to stimulate gastrointestinal maturity and function in preterm VLBW neonates, could also be evaluated [42,43,44,45,46,47]. Systematic reviews of RCTs have shown that prophylactic probiotic supplementation can significantly reduce the risk of NEC ≥ stage II and all-cause mortality while facilitating feed tolerance in preterm VLBW neonates [44,48,49]. Prebiotic oligosaccharides can modulate electrical activity and gastric emptying and may improve feed tolerance in preterm neonates [43,46].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, preterm neonates in the probiotics group had reduced risks of NEC stage ≥2 (20 RCTs, n=5529, RR 0.43, 95% CI 0.33 to 0.56) and all-cause mortality (17 RCTs, n=5112, RR 0.65, 95% CI 0.52 to 0.81), but there was no difference between groups in the risk of nosocomial sepsis (19 RCTs, n=5338, RR 0.91, 95% CI 0.8 to 1.03) 27. Probiotics also reduced the time until full enteral feeding 27 28…”
Section: Clinical Effects Of Probioticsmentioning
confidence: 99%